Pockets of Effectiveness and the Politics of State-building and Development in Africa (Oxford University Press, 2023)
Why do certain parts of the state in Africa work so effectively despite operating in difficult governance contexts? How do 'pockets of bureaucratic effectiveness' emerge and become sustained over time? And what does this tell us about the prospects for state-building and development in Africa?